Intervention and design of a strategic plan against bullying - Gongora Cheme, Roxana Katherine (Universidad Ciencia y Tecnología, 2022)
One of the most important social problems of recent times in the educational field has to do with bullying. It is evident through the media or situations that there is a presence as the problem of harassment becomes increasingly present in educational institutions. The objective of the research is the proposal to design a program of the Methodological Strategy of School Mediation to improve coexistence among schoolchildren. A descriptive methodology with a mixed design was used. It was concluded that teacher training in the identification and management of school violence is important. Proposal A aims to take advantage of all the resources necessary to increase knowledge and form complete learning in the methodological strategy of school mediation.